TRENDS IN PHILOSOPHY IN THE THIRD MILLENNIUM - Chackalackal, Saju (Journal of Dharma, 2009)
Philosophy defies precise definition, as there are innumerable ways of doing philosophy. Human ingenuity being unlimited and philosophy being a fundamental discipline that attempts to identify the rules of intellectual application, from daily chorus to the most intricate mathematical formulations that attempt to explain the complex universe as well as the miniscule subatomic particles, it is natural that we have a lot of variety in philosophical endeavours. Although certain major schools of philosophy had turned out to be the key players in the arena of any given philosophical culture, a close perusal of the history of philosophy, be it in the East or in the West, indicates that philosophical speculation has been thriving precisely because of the great variety it facilitates. Of course, paying close attention to the variety would weaken the possibility of a generalisation on what exactly philosophy is.